2012
DOI: 10.1007/s00586-012-2252-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of self-mating PEEK as an alternative bearing material for cervical disc arthroplasty: a comparison of different simulator inputs and tribological environments

Abstract: Purpose The hypothesis for this study was that the simulated wear behavior of a hydroxyapatite coated, selfmating PEEK cervical disc arthroplasty device would be dependent on the simulated testing environment. Methods Five groups of devices were evaluated under suggested ASTM and ISO load and motion profiles. The groups utilized different testing frequencies and protein content of simulator fluid, in addition to assessing the potential for third body wear. The average wear rates were determined using linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Damage to the PEEK-OPTIMA ™ femoral components was observed in the form of scratching parallel to the principal direction of sliding. Brown and Bao 3 also reported the damage to the articulating surfaces of PEEK-on-PEEK cervical discs early in a spine simulator study, however; despite the initial change in surface topography, the wear rate remained constant as observed in our study. However, there was evidence that the linear scratching on the PEEK-OPTIMA ™ femoral also caused scratching in the wear scar on the UHMWPE tibial component.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Damage to the PEEK-OPTIMA ™ femoral components was observed in the form of scratching parallel to the principal direction of sliding. Brown and Bao 3 also reported the damage to the articulating surfaces of PEEK-on-PEEK cervical discs early in a spine simulator study, however; despite the initial change in surface topography, the wear rate remained constant as observed in our study. However, there was evidence that the linear scratching on the PEEK-OPTIMA ™ femoral also caused scratching in the wear scar on the UHMWPE tibial component.…”
Section: Discussionsupporting
confidence: 61%
“…1,2 There has been growing interest in its use as an arthroplasty bearing material either in its natural, unfilled form or reinforced with carbon fibres (CFR-PEEK). Natural PEEK has been used in the spine in PEEK-on-PEEK articulations, where pre-clinical studies have demonstrated an equivalent wear rate for PEEK cervical (NuNec) 3 and lumbar disc replacements (NuBac) compared to conventional materials, 4 and although clinical follow-up has been relatively short term, the implants have shown promise. 5 CFR-PEEK has been considered for use as acetabular cups in total hip replacement, and experimental wear simulation under standard gait conditions has shown lower wear rates than cross-linked ultra-high-molecular-weight polyethylene (UHMWPE) against ceramic heads [6][7][8] although a 5-year follow-up from clinical trials of the Mitch cup has yielded a revision rate of 4 in 25 due to loosening and squeaking.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Though less extensive than cervical fusion cages, there has been investigation into the use of PEEK for cervical TDR. [6][7][8][9][10][11][12] Despite general optimism, there was concern about long-term degradation on articulating PEEK-on-PEEK surfaces. 10 This may be particularly problematic and cause uneven loading if the implant is not ideally positioned.…”
Section: Introductionmentioning
confidence: 99%
“…The use of poly ether-ether ketone (PEEK) either in its natural form or reinforced with carbon fibres (CFR-PEEK) has been considered as an arthroplasty bearing material for a number of applications including; finger joints (Joyce et al, 2006), intervertebral discs (Brown et al, 2010, Brown and Bao, 2012), acetabular cups (Wang et al, 1998, Wang et al, 2012, Scholes et al, 2008, Brockett et al, 2012) and tibial inserts (Kurtz and Devine, 2007, Scholes and Unsworth, 2009, Grupp et al, 2010). In these examples, PEEK has either been considered as an alternative to ultra-high molecular weight polyethylene (UHMWPE) or in the case of fingers and spine as a self-mating PEEK-on-PEEK bearing couple.…”
Section: Introductionmentioning
confidence: 99%